Correction to: Bilateral spontaneous thrombosis of the pampiniform plexus mimicking incarcerated inguinal hernia: case report of a rare condition and literature review - Sabyasachi Bakshi (Surgical Case Reports)
In the original publication of this article [1], there is a correction in Table 2.